Ion release dynamics of bioactive resin cement under variable pH conditions - Venkata Suresh Venkataiah; Jogikalmat Krithikadatta; Kavalipurapu Venkata Teja; Deepak Mehta; Deepak Mehta; Mukesh Doble (Frontiers in Oral Health)
IntroductionUnderstanding the ion release behaviour of bioactive resin cements is essential for evaluating their potential in restorative dentistry. Sustained ion release, especially at cariogenic pH levels, can enhance remineralization and prolong the longevity of dental restorations. This study investigates the influence of pH on the ion release profiles of a bioactive resin cement before and after recharging.MethodsDisk-shaped specimens (n = 15) of bioactive resin cement were prepared and exposed to three different pH conditions (4.5, 5.5, and 6.5) to simulate normal and cariogenic environments. Calcium ion release was quantified using atomic spectrophotometry, while fluoride and phosphate ions were analyzed using quantitative spectrophotometry. After an initial 30-day depletion phase, recharging was performed using casein phosphopeptide-amorphous calcium phosphate with fluoride (CPP-ACPF) paste.ResultsIn the pre-recharging phase (Stage 1), calcium ion release was more pronounced at acidic pH (4.5–5.5), particularly in the first five days. Fluoride and phosphate ions also demonstrated higher release at pH 4.5 and 5.5 compared to pH 6.5. Post-recharging (Stage 2) exhibited similar trends, emphasizing the role of regular recharge in sustaining ion availability. The absence of an initial burst release, commonly seen in other bioactive materials, suggests a distinct ion release mechanism in these resin cements.ConclusionThe findings highlight the pH-dependent release characteristics of bioactive resin cements and reinforce the importance of recharging for maintaining their therapeutic potential. The unique release kinetics observed may offer advantages in long-term remineralization strategies for dental restorations.